2021
DOI: 10.18632/aging.202730
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for melanoma patients on the basis of immune-related lncRNAs

Abstract: The prognosis of melanoma patients is highly variable due to multiple factors conditioning immune response and driving metastatic progression. In this study, we have correlated the expression of immune-related lncRNAs with patient survival, developed a prognostic model, and investigated the characteristics of immune response in the diverse groups. The gene expression profiles and prognostic information of 470 melanoma patients were downloaded from TCGA database. Significantly predictive lncRNAs were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Immune-related lncRNAs (irlncRNAs) have recently been studied in several cancers. Wang et al [ 9 ] identified 4 irlncRNAs to establish a risk model for lung adenocarcinoma, while 8 irlncRNAs were used to construct a prognostic model for melanoma [ 10 ]. Additionally, irlncRNAs have been utilized in glioblastoma, head and neck squamous cell carcinoma and bladder cancer [ 11–13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune-related lncRNAs (irlncRNAs) have recently been studied in several cancers. Wang et al [ 9 ] identified 4 irlncRNAs to establish a risk model for lung adenocarcinoma, while 8 irlncRNAs were used to construct a prognostic model for melanoma [ 10 ]. Additionally, irlncRNAs have been utilized in glioblastoma, head and neck squamous cell carcinoma and bladder cancer [ 11–13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports show that various lncRNAs, such as XIST, NEAT1 or NKILA, are generally involved in the regulation of human immune system and tumor-immune cell infiltration [ 215 , 216 , 217 ]. The SKCM dataset from TCGA, that comprises molecular and clinical data for 470 melanoma patients has been used recently to identify immune-related lncRNAs [ 218 , 219 ]. Ping et al have applied a modified least absolute shrinkage and selection operator (LASSO) regression model to identify 28 immune-related lncRNAs in melanoma patients, and among them, 17 pairs of co-expressed lncRNAs that could divide SKCM cohort into high-risk and low-risk groups [ 218 ].…”
Section: Lncrnas Involved In Melanoma Drug Resistance and Treatment Responsementioning
confidence: 99%
“…Moreover, the high-risk group is correlated with the expression of specific mutant genes such as BRAF and KIT ( p -value < 0.01) [ 218 ]. Wang et al have used survival analysis and Cox regression model to identify 8 immune-related lncRNAs with prognostic value in SKCM dataset [ 219 ]. Again, MIR205HG expression is linked to the poor outcome ( p -value < 0.001), and HLA-DQB1-AS1 to immune protection ( p -value = 0.048).…”
Section: Lncrnas Involved In Melanoma Drug Resistance and Treatment Responsementioning
confidence: 99%
“…Immune-related lncRNAs (irlncRNAs) have recently been studied in several cancers. Wang et al [9] identi ed 4 irlncRNAs to establish a risk model for lung adenocarcinoma, while 8 irlncRNAs were used to construct a prognostic model for melanoma [10]. Moreover, irlncRNAs have also utilized in glioblastoma, head and neck squamous cell carcinoma and bladder cancer [11][12][13].…”
Section: Backgroundsmentioning
confidence: 99%